Ducks overboard! : a true story of plastic in our oceans - Motum, Markus (Candlewick Press, 2021)
Inspired by a real incident, this look at the pollution crisis in our oceans follows one of the ducks as it is washed away on ocean currents, encountering plastic-endangered whales and sea turtles and passing through the giant floating island of marine debris known as the Great Pacific Garbage Patch. A picture book with an ultimately hopeful message about environmental issues and the state of our oceans. An end map documents the widely scattered journey of the real-life plastic ducks, showing where they have been found, as well as facts about the ways plastic is affecting various parts of the world.